1035325 Studi Deskriptif Sikap dan Pengetahuan Ibu Terhadap Perawatan Tali Pusat Pada Bayi Baru Lahir - Juliana Widyastuti Wahyuningsih (STIKes Budi Mulia Sriwijaya, 2019)
Abstract In general, the newborn's umbilical cord will collapse or fall off within one to three weeks after birth. As long as it is not separated, the baby's parents need to keep the area clean and dry. This is caused by wet and humid conditions that can increase the growth of germs that cause infection. The lack of good attitude and good knowledge of puerperal mothers for umbilical cord care in newborns makes researchers interested in conducting research. Newborns in Sukajaya Village, Sukarame District Palembang